Península Ibérica na antiguidade: o encontro entre romanos e os povos da Ibéria - Bonfá, Douglas Cerdeira (2020)
In this master's thesis we investigate the encounter between the Romans and the peoples of the Iberian Peninsula. First, we make an analysis of the concept of culture and Romanization, analyzing the context of its creation, going through its review in the post-decolonization process until arriving at more recent research. In a second moment, we analyze the work Geography of Strabo in order to search for fragments about how the author understands this process, in order to dialogue with research by contemporary specialists. Defending a multiethnic character, we use sources of material culture to interpose the idea of cultural homogeneity in Roman Hispania. Concluding our master's thesis, we present a learning object developed with digital medias with the theme Ancient Rome, to be used as support material in classes for 6th grade students of Elementary School II.